X-ray Crystallographic Studies of Dioxouranium(VI), Dioxomolybdenum(VI) and Oxovanadium(II)Complexes of o-Hydroxy Acetophenone Oxime - Mehta, B.H.; Syed, F.F. (Asian Journal of Chemistry, 2010)
The ketone o-hydroxyacetophenone was treated with hydroxylamine hydrochloride for the synthesis of its oxime derivative. The oxime was used to synthesize dioxouranium(VI), dioxomolybdenum(VI) and oxovanadium(II) complexes. Elemental analysis, molar conductivity measurements, magnetic susceptibility measrements, ESR, electronic absorption and IR absorption spectra characterized the ligand and the metal complexes. The elemental analysis reveals the metal : ligand stoichoimetry in the complexes as 1 : 2. Dioxouranium and dioxomolybdenum complexes were found to be diamagnetic, whereas oxovanadium complex was found to be paramagnetic in nature. The XRD data was to index the complexes for monoclinic system with space group P2/m. B2/m and C2/c.